The Role of Empowerment in Improving Generation Z Engagement and Performance in the Workplace - Nurmasari, Salwa Salsabila; Pala’langan, Reza; Hidayati, Retno; Lataruva, Eisha (LifeSciFi, 2025)
Generation Z is becoming a dominant force in the workforce, raising critical concerns for organizations aiming to maximize productivity and retain talent. To address this challenge, optimizing the potential of Gen Z through employee empowerment is essential. As this generation values autonomy and recognition for their contributions, employee empowerment plays a key role in enhancing both employee engagement and performance. This study explores the relationship between employee empowerment, employee engagement, and employee performance among Generation Z employees in formal sector companies in Semarang. A quantitative approach was employed, using questionnaires distributed to 100 Gen Z employees, with data analyzed through Structural Equation Modelling (SEM) using Partial Least Squares (PLS). The findings reveal strong correlation between employee empowerment, performance, and engagement. Additionally, the study emphasizes the role of employee engagement as a mediator in the connection between employee empowerment and performance, demonstrating that positioning employee engagement as a mediator is both relevant and impactful.